2016
DOI: 10.1002/prp2.270
|View full text |Cite
|
Sign up to set email alerts
|

Application of a systems pharmacology model for translational prediction of hERG ‐mediated QT c prolongation

Abstract: Drug‐induced QTc interval prolongation (Δ QTc) is a main surrogate for proarrhythmic risk assessment. A higher in vivo than in vitro potency for hERG‐mediated QTc prolongation has been suggested. Also, in vivo between‐species and patient populations’ sensitivity to drug‐induced QTc prolongation seems to differ. Here, a systems pharmacology model integrating preclinical in vitro (hERG binding) and in vivo (conscious dog Δ QTc) data of three hERG blockers (dofetilide, sotalol, moxifloxacin) was applied (1) to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…and V 1A receptors could be further investigated. The applicability of such a system-pharmacology approach to explaining differences between hERG-mediated QTC prolongation in adults and neonates on the basis of modelpredicted differences in target expression levels, which were consistent with experimentally derived mRNA levels in patients (Moric-Janiszewska et al, 2011), has been recently demonstrated (Gotta et al, 2016).…”
Section: Figuresupporting
confidence: 61%
“…and V 1A receptors could be further investigated. The applicability of such a system-pharmacology approach to explaining differences between hERG-mediated QTC prolongation in adults and neonates on the basis of modelpredicted differences in target expression levels, which were consistent with experimentally derived mRNA levels in patients (Moric-Janiszewska et al, 2011), has been recently demonstrated (Gotta et al, 2016).…”
Section: Figuresupporting
confidence: 61%
“…The majority of these neglect the intertwined dependencies across cardiovascular measures, making comparison of results difficult. For instance, gamma parameters in Tables 4 and 5 were generally lower than previously reported values in human (Chu et al, 1999;Duffull et al, 2000;Mehrotra et al, 2007;Gotta et al, 2016), generally reported to be ≥1, but it is unclear whether this stems from differences in species or model. A few studies (Francheteau et al, 1993;Upton and Ludbrook, 2005;Snelder et al, 2014;Kamendi et al, 2016) have applied an integrative approach including inter-relationships between TPR, SV, and MAP.…”
Section: Pharmacodynamic Modelmentioning
confidence: 63%
“…A recent evaluation of a Transient Receptor Potential Melastatin-8 blocker showed threefold cross-species (mouse versus dog) differences in its potency, resulting in clinically important differences in core body temperature predictions [57]. In another study, the E max and EC 50 for prolonging the QT-interval were found to differ between humans and dogs [58]. A third publication showed that the affinity of psychoactive drugs differed significantly between, for example, the D1 rat and 5HT2 rat , and D1 human and 5HT2 human receptors [9].…”
Section: Interspecies Scalingmentioning
confidence: 99%